Evaluation of Learning in Hybrid Learning in Sports Physiology Course - Mimi Yulianti; Leni Apriani; M. Fransazeli Makorohim (JUARA : Jurnal Olahraga, 2022)
The background of the problem in this study is that there has never been an evaluation of learning using hybrid learning. This study aimed to determine the results of the hybrid learning evaluation during the Covid-19 pandemic in the Sports Physiology Course. The method used in this research is descriptive quantitative. Data collection was used by distributing research questionnaires. Based on the results of the study, it can be concluded that the Evaluation of Hybrid Learning in the Covid-19 Pandemic Period in the Sports Physiology Course, with a percentage of 75%, is in the range of values between 62% - 76% in the Medium category. So it can be concluded that the results of the evaluation of hybrid learning in the exercise physiology course are Moderate/Enough because many students choose face-to-face learning.